1979
DOI: 10.1017/s0014479700000594
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Limiting Yields of Tea (Camellia sinensis)

Abstract: Measurements indicate that the tea crop-which consists of young shoots-is sink-limited and that the plucking of immature shoots, essential for quality tea, is a major factor limiting yields of the crop. The importance of this aspect in selecting for high-yielding plant material is discussed.The world tea crop comes from the perennial shrub Camellia sinensis L. The quantity of tea produced from clonal bushes is increasing, but the bulk of the crop comes from unselected or poorly selected planting material, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 3 publications
(2 reference statements)
3
36
0
1
Order By: Relevance
“…2-3 leaves and a bud) is only a small fraction (0.05-0.15) of its total biomass production (Callander, 1978;Tanton, 1979). Therefore, both Tanton (1979) and Squire and Callander (1981) argued that assimilate supply cannot be a limiting factor in yield determination, when harvested yield is such a small fraction of total biomass production. Instead, tea leaf yield per unit land area is strongly correlated with N sh .…”
Section: Importance Of Photosynthetic Capacity In Yield Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…2-3 leaves and a bud) is only a small fraction (0.05-0.15) of its total biomass production (Callander, 1978;Tanton, 1979). Therefore, both Tanton (1979) and Squire and Callander (1981) argued that assimilate supply cannot be a limiting factor in yield determination, when harvested yield is such a small fraction of total biomass production. Instead, tea leaf yield per unit land area is strongly correlated with N sh .…”
Section: Importance Of Photosynthetic Capacity In Yield Determinationmentioning
confidence: 99%
“…Instead, tea leaf yield per unit land area is strongly correlated with N sh . Hence, Tanton (1979) concluded that tea yield is sinklimited rather than source-limited. Based on the results of a simulation model, Matthews and Stephens (1998a) also suggest that assimilate supply is unlikely to limit shoot growth under most conditions.…”
Section: Importance Of Photosynthetic Capacity In Yield Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…For solar radiations above 350 Wm -1 require 700-800 Wm -1 , a value equivalent to full sunlight in the cooler seasons of many high altitude tea areas, and account for 75% of full sunlight in the warmer rainy seasons. The factors that have been documented to limit yield include: removal of young shoots (Tanton, 1979), air temperature (Ng'etich, Stephens, & Othieno, 2001); Tanton, 1982a;, soil temperature confounded with dry air (Tanton, 1982a;Odhiambo, Nyabundi, & Chweya, 1993;Chen & Fong, 1994;Nixon, Burgess, Sanga, & Carr, 2001), hail (Ng'etich et al, 2001;Othieno et al, 1992), day-length (Tanton, 1982b), soil temperature (Ng'etich et al, 2001) and solar radiation (Squire, 1977). Falling temperatures and soil physical and chemical conditions greatly limits tea yield (Ng'etich et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Tea bushes may therefore have an inadequate number of growing shoots to use photo-assimilates produced by photosynthesis (Mohotti & Lawlor, 2002;Squire, 1977;Tanton, 1979). This situation is likely to be exacerbated under continuous mechanical harvesting, where removal of shoots is indiscriminate of age and often the strongest sinks are removed, which are the single buds and single leaf and a bud (Manivel and Hussain 1986).…”
Section: Introductionmentioning
confidence: 99%